PENGARUH PEMANFAATAN SARANA BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR - Arnold Rama Ardiansyah; Yon Rizal; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2014)
This study aims to determine the effect of the utilization of facility in school and learning motivation toward learning outcomes of IPS Terpadu subject. The population are 329 students. The research is a sample study with a total of 177 people of 329 people in the research using the formula Cochran. Data collection techniques are using question form. The method in this research is associative with ex post facto and surveys approach. The first and the second hypothesis were tested by using simple linear regression. The third hypothesis is using multiple linear regression. Based on the analysis of the data obtained, the results are: (1) there is an effect of the utilization of facility in school on learning outcomes toward IPS Terpadu, (2) there is an effect of the motivation toward learning outcomes of IPS Terpadu, (3) there is an effect of the utilization of facility in school and motivation toward learning outcomes of IPS Terpadu subject. Penelitian ini bertujuan untuk mengetahui pengaruh pemanfaatan sarana belajar di sekolah dan motivasi belajar terhadap hasil belajar IPS Terpadu. Populasi penelitian berjumlah 329 siswa. Penelitian ini adalah penelitian sampel dengan jumlah 177 orang sampel dari 329 orang yang dicari dengan menggunakan rumus Cochran. Metode penelitian ini adalah asosiatif dengan pendekatan ex post facto dan survey. Teknik pengumpulan data dengan menggunakan angket. Pengujian hipotesis pertama dan kedua menggunakan regresi linier sederhana. Pengujian hipotesis ketiga menggunakan regresi linier multiple. Berdasarkan analisis data diperoleh hasil penelitian sebagai berikut: (1) Ada pengaruh pemanfaatan sarana belajar di sekolah terhadap hasil belajar IPS Terpadu, (2) Ada pengaruh motivasi belajar terhadap hasil belajar IPS Terpadu, (3) Ada pengaruh pemanfaatan sarana belajar di sekolah dan motivasi belajar terhadap hasil belajar IPS Terpadu. Kata kunci: hasil belajar, motivasi belajar, sarana belajar